A new species of Ephoron Williamson, 1802 (Ephemeroptera: Polymitarcyidae) from Thailand - Techakijvej, Chotiwut; Sareein, Nattawut; Hwang, Jeong Mi; Bae, Yeon Jae; Phalaraksh, Chitchol (Zootaxa, 2021)
The genus Ephoron Williamson, 1802 is widely distributed around the world. In Thailand, only Ephoron indicus Pictet, 1843 was reported in 1961. In this study, a new Ephoron mayfly is described as Ephoron ookaewae sp. nov. In this new species description, the morphological characteristics of larvae and eggs in addition to adults are also shown in detail. Number of tubercles on mandibular tusks, and a median frontal process in larvae, distinguish Ephoron ookaewae sp. nov. from other Ephoron species. Their polar cap shape and a concave indentation in their eggs are also unusual. In addition, the mitochondrial DNA COI sequence data of the newly described Ephoron ookaewae sp. nov. is registered in GenBank. Registration of sequence data for the DNA barcode region of Ephoron mayflies inhabiting the Oriental region remains limited, however it will be useful for future research.